817 Effectiveness of volunteer based first responder program for preventing drowning in rural Bangladesh. (1st September 2016) - Hossain, Mohammad Jahangir; Mecrow, Tom; Rahman, Fazlur; Ahamed, Imtiaz; Baset, Kamran Ul; Biswas, Animesh; Rahman, Aminur
Abstract : Background: Health care facilities in rural areas are challenging in most developing countries. Bangladeshi people exposes to water for their daily life as a result child mortality & morbidity due to drowning is higher than any other causes. In this paper trained community volunteers provided First responder services in managing drowning causalities were described. Objective: Assessment of the First Aid services provided by community volunteers in managing of drowning causalities in rural Bangladesh. Methodology: To deliver first aid services under SwimSafe program 1644 adolescent (male-741, female-903) were trained in different districts of Bangladesh. All volunteers received 2 days training using manual adopted from IDRC-B. All trainees had access of manikins to practice CPR. All volunteers were also trained on record keeping about the first aid services they provide. Trainings were conducted in between May to September and at the end of the year data was collected from the volunteers. Results: reports were collected from 844 instructors and services were provided among 4, 648 causalities, of them 79 were due to drowning. Among the drowning causalities 70 were children. CPR was given to manage 23 causalities, among them 21were children and 2 were adults. Of all 21 children 76% (n = 16) survived and 24% (n = 5) died. All the children were within 10 years of age. Volunteers treated 56 drowning casualties with keeping recovery position, of them 30 were boys & 26 were girls. Among the 56 causalities 80% (n = 49) were children. Of all drowning causalities 48 were referred for further treatment. Conclusion: Bangladesh is a disaster prone area and the access of health care providers is very difficult in rural areas of Bangladesh so by developing adolescent based first responder it is possible to reduce drowning related mortality, morbidity disability. Acknowledgement: Contribution of UNICEF is acknowledged